On the issue of complicity in a crime with a special subject: on the example of corruption crimes - Khassenova, A.R.; Kudryavtseva, A.V. (Bulletin of the Karaganda University “Law Series”, 2019)
Іn the article on the example of corruption crimes, the problem of qualification of criminal offenses committed by a special subject in complicity with a common subject is considered. It is stated that the criminal legislation in the current version does not provide for the qualification as co-execution of the actions of the General subject, which actually make up the objective side of the criminal offense committed by the accomplices. This does not allow for an objective characterization of such acts, thereby preventing a proper legal assessment of the act committed and the imposition of a punishment corresponding to the nature and extent of the person's actual participation in its Commission. It is concluded that it is necessary to change part 5 of article 29 of the criminal code, providing for a person who does not have the features of a special subject, the ability to act not only as an organizer, instigator and helper, but also as a co-executor. A new version of this article is proposed. Also the question of qualification of the corruption crimes committed in group of persons by preliminary arrangement is considered. The conclusion is substantiated that in cases where at least two subjects of corruption offenses participated in such crimes, the qualifying sign — «Commission of the act by a group of persons by prior agreement» — is subject to imputation regardless of what types of accomplices they are.